Pseudotumor of Ciliary Body - Mary Varghese; Raghavendra Ramappa; Sripathi Kamath (Case Reports in Ophthalmological Medicine)
Orbital pseudotumor is a benign disease involving the orbital structures. Pseudotumor of the ciliary body is rare. We present a case of a 27-year-old male who presented with gradual visual loss, pain, and redness in his left eye. On examination he was found to have a yellowish white mass at the periphery of anterior chamber in his left eye and ultrasound biomicroscopy (UBM) revealed a ciliary body mass in the same eye. He was treated with systemic steroids, which was tapered over a period of 8 weeks. His symptoms improved and the ciliary body mass disappeared with no recurrence over the next 6 months. UBM is an important diagnostic tool for diagnosing ciliary body mass. Early diagnosis and prompt treatment with systemic steroids may help resolve pseudotumor of the ciliary body.